Andrographolide‐loaded solid lipid nanoparticles enhance anti‐cancer activity against head and neck cancer and precancerous cells. (20th December 2020) - Li, Hongquan; Qu, Xingzhou; Qian, Wenhao; Song, Yang; Wang, Changhong; Liu, Wei
Abstract: Background: Increasing evidence indicates that andrographolide (ADG) exhibits anti‐cancer activity against various cancer cell lines. However, its high hydrophobicity and poor bioavailability restrict its clinical application as a chemopreventative agent. Previously, we have shown that ADG‐loaded solid lipid nanoparticles (SLNs) significantly enhanced the bioavailability and anti‐hyperlipidemic activity of ADG. Objectives: We aimed to investigate whether ADG‐SLN enhanced the bioavailability and anti‐cancer efficacy of ADG in the human immortalized oral epithelial (HIOEC), precancerous leukoplakia (Leuk1), HN6, and HN30 cells that represented an in vitro model of stepwise head and neck squamous cell carcinoma development. Results: The 50% inhibitive concentration (IC50) of ADG‐SLN was significantly lower than that of free ADG against HIOEC, Leuk1, and HN6 and HN30 cells. Moreover, ADG‐SLN was more effective than free ADG in promoting cell cycle arrest and apoptosis. Importantly, intracellular absorption of ADG was significantly higher in HN6 cells treated with ADG‐SLN compared with free ADG‐treated cells. Conclusions: Our preliminary study demonstrates that ADG‐SLN exhibits superior inhibitory activity against head and neck cancer and precancerous cells compared with free ADG. This effect is due to the higher efficiency of cellular uptake and intracellular absorption by ADG‐SLN.